2020
DOI: 10.1097/jcp.0000000000001284
|View full text |Cite
|
Sign up to set email alerts
|

Polaprezinc (Zinc–l-Carnosine Complex) as an Add-on Therapy for Binge Eating Disorder and Bulimia Nervosa, and the Possible Involvement of Zinc Deficiency in These Conditions

Abstract: Background Zinc plays an important role in appetite regulation. l -Carnosine, an endogenous dipeptide, may also regulate eating behavior via its histaminergic and antiglutamatergic properties. Polaprezinc (zinc– l -carnosine complex) is a medication for gastric ulcers. A small case series reported successful treatment of binge eating with add-on polaprezinc. Methods This was an open trial of add-on polaprezinc in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…Zinc deficiency is exhibited in a variety of clinical manifestations. It has been reported that it causes various symptoms, such as dermatitis, diarrhoea, immunocompromised hostism, hypogonadism in men, delayed wound healing and dysgeusia (14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc deficiency is exhibited in a variety of clinical manifestations. It has been reported that it causes various symptoms, such as dermatitis, diarrhoea, immunocompromised hostism, hypogonadism in men, delayed wound healing and dysgeusia (14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Die "Zinkmangelhypothese" wurde auch auf die BN und BES angewendet. Eine rezente Pilotstudie berichtet von reduzierten Essanfällen und weiteren positiven Effekten durch Polaprezink (Kombination aus Zink und l-Carnosin) als Zusatztherapie [23]. Trotz möglicher theoretischer Wirkmechanismen kann der Einsatz von Ketamin aufgrund bisher empirisch nicht gesicherter Wirksamkeit und dem Sicherheitsprofil bei Patient*innen mit AN nicht empfohlen werden.…”
Section: Anorexia Nervosaunclassified
“…In addition, Zn has been shown to affect glutaminergic and serotonergic regulation as well as neuroproliferation and systemic anti-inflammatory effects [64][65][66][67]. In a study of patients with eating disorders, Zn levels were found to be reduced [68]. Rosenblum also described a case of Zn deficiency-induced cardiomyopathy in a patient diagnosed with acute phase AN in whom other possible etiopathogenetic factors were excluded.…”
Section: Vitamins and Microelementsmentioning
confidence: 99%